Incubation and Intuition in Creative Problem Solving - Gilhooly, Kenneth J. (Frontiers in Psychology, 2016)
Creative problem solving, in which novel solutions are required, has often been seen as involving a special role for unconscious processes (Unconscious Work) which can lead to sudden intuitive solutions (insights) when a problem is set aside during incubation periods. This notion of Unconscious Work during incubation periods is supported by a review of experimental studies and particularly by studies using the Immediate Incubation paradigm. Other explanations for incubation effects, in terms of Intermittent Work or Beneficial Forgetting are considered. Some recent studies of divergent thinking, using the Alternative Uses task, carried out in my laboratory regarding Immediate v. Delayed Incubation and the effects of resource competition from interpolated activities are discussed. These studies supported a role for Unconscious Work as against Intermittent Conscious work or Beneficial Forgetting in incubation. What form might unconscious work take? On theoretical grounds, the notion that Unconscious Work involves the same processing steps as Conscious Work but minus conscious awareness is discounted, despite some recent arguments that the unconscious can duplicate any conscious function. A candidate account in terms of spreading activation, coupled with below-threshold but active goal representations, is put forward. This account could explain the emergence of subjectively sudden intuitive solutions (Aha-insight solutions) as a result of unconscious processes (Unconscious Work) during incubation periods.